The Use of Betong Bamboo as Reinforcement of Concrete Beam Structures - Yazid, Nur Syarafana; Zuraidi, Rozalinda; Noor Hisham, Nurul Ain; Salman Salim,; Nornajihah Mohammad Yazid, (Multidisciplinary Applied Research and Innovation, 2023)
In the endemic era, the source and cost of steel  is increased. The quality of material used in the construction field is important as it determines the strength of the building. Hence, this project aims to utilize the betong bamboo as reinforcement for concrete beam structures. There are three different sizes of bamboo strips used. Next, the chemical treatment is conducted in order to  protect the bamboo from any insects such as termites. A variety of testing are involved in the bamboo reinforcements such as compression, tensile, shear, and static bending test to get a more accurate result. However, the testing found that the product is failed. This project is failed due to honeycombs found around the beam and only one test can be done. Hence, it can be solved by preparing the sample of concrete mix well. Based on the findings, it can be concluded that the use of steel in construction buildings is better because steel is not easy to get damaged by insects compared to bamboo.